THE STRUGGLE OF SOCIO-POLITICAL ORGANIZATIONS CREATED BY SOUTH AZERBAIJANIS FOR THEIR FIRST LANGUAGE (1979-2005) - HAJIYEVA, YEGANA AZIZ (PEARSON JOURNAL, 2020)
The article deals with the policy of assimilation carried out at the state level against non-Persian peoples living in the Islamic Republic of Iran in 1979-2005, including the rights of Azerbaijani Turks to their first language. The article notes that after the victory of the revolution, the attitude of the political, socio-political organizations formed by the Azerbaijani Turks in Iran to the options for resolving the national issue at these stages differs depending on events in the world and the region, as well as the existing socio-political atmosphere in Iran. In their opinion, increasing the functionality of the Azerbaijani language and giving it official status is a more pressing issue against the background of other problems.